2015
DOI: 10.1002/lno.10062
|View full text |Cite
|
Sign up to set email alerts
|

An inland sea high nitrate‐low chlorophyll (HNLC) region with naturally high pCO2

Abstract: We present a time series of data for temperature, salinity, nitrate, and carbonate chemistry from September 2011 to July 2013 at the University of Washington's Friday Harbor Laboratories. Samples were collected at the Friday Harbor dock and pump house. Seawater conditions at Friday Harbor were high nitrate-low chlorophyll, with average nitrate and pCO 2 concentrations of 25 6 5 lmol L 21 and 700 6 103 latm (pH 7.80 6 0.06). Transient decreases in surface water nitrate and pCO 2 corresponded with the timing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 69 publications
6
61
0
Order By: Relevance
“…The pCO 2 levels in the medium and high treatments are higher than the end-of-century projections for the 'rapid economic growth' (IPCC 'A1' scenarios, IPCC 2007IPCC , 2014. For example, pCO 2 averaging 700 (pH = 7.8), but ranging from lower than 400 to higher than 1,000, have been observed in seawater collected weekly between July 2011 and July 2013 from coastal waters within 20 seaway km of our eelgrass collection site and <1 km from other eelgrass beds (Murray et al 2015). For example, pCO 2 averaging 700 (pH = 7.8), but ranging from lower than 400 to higher than 1,000, have been observed in seawater collected weekly between July 2011 and July 2013 from coastal waters within 20 seaway km of our eelgrass collection site and <1 km from other eelgrass beds (Murray et al 2015).…”
Section: Experimental Set-upmentioning
confidence: 68%
See 1 more Smart Citation
“…The pCO 2 levels in the medium and high treatments are higher than the end-of-century projections for the 'rapid economic growth' (IPCC 'A1' scenarios, IPCC 2007IPCC , 2014. For example, pCO 2 averaging 700 (pH = 7.8), but ranging from lower than 400 to higher than 1,000, have been observed in seawater collected weekly between July 2011 and July 2013 from coastal waters within 20 seaway km of our eelgrass collection site and <1 km from other eelgrass beds (Murray et al 2015). For example, pCO 2 averaging 700 (pH = 7.8), but ranging from lower than 400 to higher than 1,000, have been observed in seawater collected weekly between July 2011 and July 2013 from coastal waters within 20 seaway km of our eelgrass collection site and <1 km from other eelgrass beds (Murray et al 2015).…”
Section: Experimental Set-upmentioning
confidence: 68%
“…All replicates were dosed with 33 units/mL Penicillin and 33 ug/mL Streptomycin at the time of the disease challenge in order to prevent bacterial coinfection (e.g., Burge and Friedman 2012). While each phase had different pCO 2 inputs, the ambient treatments in phases I and II are within the range of values currently being recorded in coastal waters in the San Juan Archipelago (Murray et al 2015). All treatments were held at 15°C.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Reloncaví Fjord, at the study area, was found to be a smaller CO 2 source than fjords in the Northern Hemisphere at higher latitudes, like Roskilde Fjord, North Zealand, Denmark, which has been reported to be an annual CO 2 source (3.9 mol CO 2 ·m −2 ·year −1 ; Mørk et al, ), and Koljo Fjord, Sweden, which also showed a marked transition in p CO 2 dynamics from autumn to spring (Atamanchuk et al, ). In Friday Harbor in the glacially formed San Juan Archipelago (Washington, USA), p CO 2 ranged from ~300 to ~1,100 μatm over a 2‐year period, mostly with high positive Δ p CO 2 , suggesting that the sea is a source for atmospheric CO 2 in this area (Murray et al, ). On the other hand, Kongsfjorden and Tempelfjorden Arctic fjords (Svalbard, Norway) appeared to be less variable systems (in terms of the carbonate dynamics and saturation state of Ω Arag ) and they apparently act as CO 2 sink systems (Fransson et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Water samples were analyzed for alkalinity and dissolved inorganic carbon at the FHL Ocean Acidification Environmental Laboratory (Dickson et al ; Riebesell et al ), and used to calculate pH in CO2calc (ver. 2013; Murray et al ). Error between Durafet pH and calculated sample pH was 0.06 pH units (root mean square error, n = 4), and sensor was 0.04 pH units (RMS error in tris buffer, n = 8), and was considered sufficient to capture dynamics in pH (range 8.07–7.72 in Summer 2013, Spring 2014).…”
Section: Methodsmentioning
confidence: 99%